SUSTAINABILITY IN THE MINING TOWN: DOES THE GHOST TOWN IS REAL? - Sulistiyohadi Sulistiyohadi; Moersidik Moersidik; Suparmoko Suparmoko (MESP–FEB UNS, 2016)
Coal booming in the last ten years, made the mining industry as the backbone of the mining town. This study aims to assess sustainability at Berau and Paser District in East Kalimantan Province as a mining town; wherein 2024 the mining industry will enter the stage of post-mining. Sustainability cities assessed by comparison of GDP sectors making up the structure of the economy. The methodology is made by depth interviews with stakeholders such as Regent, mining manager and community leaders. The results showed that Berau and Paser as mining town did not sustain and failed to perform the transformation of non- renewable natural resources to empower the human resources. In last five years, the quality of Berau people more than 60% graduated from junior high school. It is not enough to make the growth sustainability. Human interaction from the outside as the miners had formed multiplier economic effect, where it fostered social and economic interaction higher than the socio-economic interaction between the local residents. Migrating miners will reduce economic rents that have been built since 1993. The potential for a real ghost town will occur after the end of mining activities although that conditions ghost town in Paser and Berau's not like in America and Europe. This condition would make the collapse of economics interaction that has been built over the years. Keywords : mining town, ghost town, sustainability, Berau, Paser.